Pengendalian Internal Pada Perusahaan Start Up - Regita M Farhana; Ludwina Harahap (AKURASI: Jurnal Riset Akuntansi dan Keuangan, 2020)
Internal Control System is one of the tools for management to control all operational activities in line to achieve ultimate goals. As a start-up company, internal control is a must. This research conduct to analyzes internal control systems in handling inventory of vegetables and fruit-based on COSO (Committee of Sponsoring Organization) theory. This type of research is a qualitative descriptive approach. Data is obtained through interviews with informants. The results showed that the company has largely implemented internal controls on vegetable and fruit inventory that according to internal control standards according to COSO. But, it is not fully implemented for environmental control and supervision activities.